1965
DOI: 10.1071/ea9650052
|View full text |Cite
|
Sign up to set email alerts
|

Sorbed phosphate at standard supernatant concentration as an estimate of the phosphate needs of soils

Abstract: Phosphate sorption capacity of soils has meaning only if the equilibrium supernatant solution concentration is specified. Measurements have been made, on a variety of Queensland soils, at an equilibrium concentration of 0.2 p.p.m. P ; reasons for this choice of cencentration are discussed. Phosphate sorption values measured in this way appear to parallel the phosphate needs of legumes growing on a number of the soils examined in the laboratory. The approach is put forward for testing by others on present and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
6

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(40 citation statements)
references
References 0 publications
1
33
0
6
Order By: Relevance
“…The current study revealed that the recommended P fertilizer of 26 kg P ha -1 for maize production (Kenya Agricultural Research Institute, 1994) was not adequate for optimum maize production at all these sites. This was because it could only supply at most 11.6 mg kg -1 which was much below soils P sorption capacities of 107 to 402 mg P kg -1 (Figure 1) required to obtain the recommended solution concentration of 0.2 mg L -1 that is considered adequate for most crops (Beckwith, 1965). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study revealed that the recommended P fertilizer of 26 kg P ha -1 for maize production (Kenya Agricultural Research Institute, 1994) was not adequate for optimum maize production at all these sites. This was because it could only supply at most 11.6 mg kg -1 which was much below soils P sorption capacities of 107 to 402 mg P kg -1 (Figure 1) required to obtain the recommended solution concentration of 0.2 mg L -1 that is considered adequate for most crops (Beckwith, 1965). …”
Section: Discussionmentioning
confidence: 99%
“…Because of its importance, several tests have been developed for soil available P determination; however, they do not provide information on soil P sorption capacities (Fixen & Grove, 1990). Therefore, P sorption isotherms which relate P concentration in soil solution to soil sorbed P have been developed to predict P fertilizer requirements for crops (Beckwith, 1965;Fox & Kamprath, 1970). The most widely used model to predict relationships between fixed and solution P is the Langmuir equation (Cabrera et al, 1977;Ryden & Syers, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of P that needs to be added to bring soil to an equilibrium solution concentration of 0.2 ttg P ml 1 has been suggested as the basis for characterising the P adsorption capacity of soils. This concentration is based on the suggestion made by Beckwith [1] that this equilibrium P concentration (0.2/zgPml -) in solution cultures was adequate for optimum growth of many crops [15]. However, at times this approach of equilibrium P solution concentration may over-estimate the P requirement of soils and generalization would be hazardous [4].…”
Section: Phosphorus Adsorptionmentioning
confidence: 99%
“…However, P in soil solution is not the only source available to plants, because as absorption occurs, solution P is constantly replenished by dissolution of labile P, which maintains the balance of P in soil solution (Raij, 2011). Studies have shown that the determination of P in solution, which varies according to the characteristics of each soil, is not a good single indicator of P availability to plants, (Beckwith, 1965;Smyth & Sanchez, 1980;Novais et al, 2007). Still, further research on P in nutrient solution is important to understand the development pattern of the plant and evaluate the influence of P on the other nutrients, since the growth-stimulating P concentrations in nutrient solution are usually higher than the P levels in the soil solution.…”
Section: Introductionmentioning
confidence: 99%